Occurrence and isolation of some Fusarium species associated with crown and root rot disease in some wheat fields of Duhok, IKR, Iraq - Al-Tovi, Bareen Sidqi Shareef; Haleem, Raed Abduljabbar (Sulaimani Journal for Pure and Applied Sciences, 2018)
The current work was conducted on crown and root rot disease of wheat incited by Fusarium species. A survey was carried out in several wheat fields at Sumel, Duhok province including: (Camone, Hajsne, Namrik, Sharia and Sumel center) during booting and heading stages of wheat in April to May and Ripening in May to Jun during the growing season 2014/15. The symptoms were obvious in all the locations as yellowing, stunting, and browning discoloration of lower stems and roots. The highest disease incidence in both stages was found in Hajsne (67.2% and 74.4%, respectively), while the lowest disease incidence was recorded in Camone (21.6%) at the first survey and increased to (41.6%) in the second survey in Namrike. Fusarium graminearum, F. oxysporum, F. solani, F. avenaceum, and F. nivale were isolated from root and crown of wheat. F. graminearum was isolated at high frequency (56%) followed by F. oxysporum (23%). The prevalence of Fusarium species was varied with concern to locations. The highest prevalence of F. graminearum was reported in Camone (70%) followed by Namrike (64%) and the lowest prevalence found in Sumel center (29%), while F. oxysporum and F. solani were the superior species in Sumel center (36%) and Hajsne (22%) respectively. Fusarium spp. were isolated from all wheat fields in both stages, at (Booting to Heading) it was higher accumulated in roots with (42%), increased to (58%) in the (Ripening) which mostly isolated from crown. Pathogenicity test of isolated Fusarium species was performed in greenhouse. F. graminearum, F. oxysporum and F. solani resulted more disease incidence and severity than remaining tested species with obvious symptoms of crown and root discoloration, reducing of wheat growth and wilting.
Keywords: Fusarium species; Crown and Root Rot; Field survey; Morphological Identification; Wheat